Exposure to violence and aggression in secondary school students from educational institutions from the Chancay district - Romero Dioses, Ayrton Miguel (2019)
The objective of the present investigation is to establish the relation of exposure to violence and aggression in high school students of educational institutions of the district of Chancay, Lima provinces. The sample consisted of 460 students, from 12 to 17 years old, both sexes, and from 1 to 5th year of secondary school. The questionnaire on exposure to violence in childhood and adolescence of Orué and Calvete (2010) and the Agression Questionnaire (AQ) of Buss and Perry (1992) were used. It is found that there is a significant positive and direct relationship between exposure to violence and aggression (p <0.000; r = 0. 621 **), as for the correlations, these are significant positive and moderately between the television, community dimensions, home and school of exposure to violence, and aggression (p <0.000; r = .577 **, r = .473 **, r = .614 ** and r = .614 **) Also, it was determined that 59% of students were moderately exposed to situations of violence, while 49% of them have a high level of aggression.